2020
DOI: 10.4103/ijem.ijem_212_20
|View full text |Cite
|
Sign up to set email alerts
|

Persistent elevation of parathormone levels after surgery for primary hyperparathyroidism

Abstract: Background: Persistent elevation of serum parathyroid hormone (PTH) despite normocalcemia have been documented in 8- 40% of patients after parathyroidectomy. We hereby report our experience from different centers across India to determine clinical significance of postoperatively elevated PTH levels and review relevant literature. Methods: We conducted a retrospective case series study and reviewed all the patients who underwent surgery for primary hyperparathyroidism (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Persistent hyperparathyroidism (P-HPT) is defined as the condition where calcium either does not return to normal values or rises again within 6 mo of the initial parathyroidectomy for pHPT[ 8 ]. It is mainly due to failure to remove an overactive parathyroid (adenoma or unrecognized parathyroid hyperplasia)[ 8 , 10 , 11 ]. Recurrent hyperparathyroidism (R-HPT) occurs when calcium increases beyond normal limits after at least 6 mo of normal values after the initial parathyroidectomy for pHPT.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent hyperparathyroidism (P-HPT) is defined as the condition where calcium either does not return to normal values or rises again within 6 mo of the initial parathyroidectomy for pHPT[ 8 ]. It is mainly due to failure to remove an overactive parathyroid (adenoma or unrecognized parathyroid hyperplasia)[ 8 , 10 , 11 ]. Recurrent hyperparathyroidism (R-HPT) occurs when calcium increases beyond normal limits after at least 6 mo of normal values after the initial parathyroidectomy for pHPT.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5] A study from India reported PPTH elevation 30% of patients for several years post parathyroid adenectomy. 6 Several factors have been implicated for this persistent elevation of PTH, including low vitamin D (vit-D) levels, impaired renal function, a secondary response to bone remineralization, ectopic gland location, errors in frozen section, in-experienced surgeon, presence of persistent disease and development of another autonomous Conflict of interest: The authors declared no conflict of interest exists. Citation: Ahsan T, Ghaus S, Pal KMI, Erum U, Jabeen R. Persistently elevated parathyroid hormone level after curative parathyroidectomy in patients with primary hyperparathyroidism.…”
Section: Introductionmentioning
confidence: 99%